Answer:
The sum of the first six terms is 38.39
Step-by-step explanation:
This is a geometric sequence since the common difference between each term is
Thus,
To find the sum of first six terms, we need to find the fifth and sixth term of the sequence.
To find the fifth term:
The general form of geometric sequence is
To find the fifth term, substitute in
To find the sixth term, substitute in
To find the sum of the first six terms:
The general formula to find Sn for is
Thus, the sum of first six terms is 38.39
Answer:
m =
Step-by-step explanation:
=> (-11/6) + m = -2/9
Adding 11/6 to both sides
=> m =
LCM = 18
=> m =
=> m =
<span>The process of solving the inequality will be:
-2(5 - 4x) < 6x - 4
8x - 10 < 6x - 4
-6 < -2x
x > 3
This is in accordance to the rule of solving inequalities which states that whenever we multiply or divide by a negative number while solving an inequality, we must reverse the inequality sign.
The last option is correct.</span>
Divide the number of ice-cream bars into the number of people. Example: say you have 20 ice cream bars and 10 people you divide 20/10 and get 2 ice cream bars per person. Hope this helped.